Norm Pritchard plays Australian and German folk music in the John Meredith folklore collection - Pritchard, Norm, 1914-; Meredith, John, 1920-2001. (1987)
Folkloric recording. Norm Pritchard plays Australian and German folk music on a Bussilaccio 2-row accordion.
Also available online
Keywords: Pritchard, Norm, 1914- -- Interviews; Accordionists -- Australia; Folk music -- Australia; Folk music -- Germany; Folk songs, German -- Australia; Accordion music